Pemanfaatan Epistemic Network Analysis sebagai Pendukung Analisis Sentimen dalam Collaborative Learning - Roy Parsaoran; Jonathan Bernad; Tifani Astadini; Hapnes Toba; Maresha Caroline Wijanto; Mewati Ayub (Indonesia Association of Computational Linguistics (INACL), 2020)
A lot of blended learning methods have been applied to modern learning system. One of the most used learning methods is collaborative learning which combines and extends group discussion. The recorded data during a collaborative learning session could be useful to enhanced the interaction among the class members, including the lecturer. Using sentiment analysis, the discussion can be categorized whether the discussion goes well or not, it can also be seen which group members are most active and have a positive impact on the work assigned to the group. In this preliminary research, sentiment analysis approach will be combined with Epistemic Network Analysis (ENA) so that it can see a graphical depiction of each member's contribution in a group discussion. Our experimental results show that ENA displays better insights of the students activities than only using the sentiment analysis.